Political Legitimacy and Representation in Al-Mawardi’s Political Thought: Reinterpreting the Concept of Ahl al-Ḥall wa al-‘Aqd in Modern Representative Democracy - Ananda, Yudha Tama Dwi; Qohar, Abd.; Yudha (Scopus ID: 57205266060), Gesit (Universitas Islam Negeri Raden Intan Lampung, 2026)
Political legitimacy and representation have become fundamental issues in contemporary democracy, particularly amid declining public trust, weakening political accountability, and rising demands for higher-quality representative institutions. Within this context, Al-Mawardi’s political thought offers a normative perspective that remains highly relevant, although it has generally been interpreted as a model of classical Islamic political institutions. This study aims to examine the concepts of political legitimacy and representation in Al-Mawardi’s political thought and to reinterpret the concept of Ahl al-Hall wa al-‘Aqd. Employing a qualitative library research approach, the study analyzes Al-Aḥkam al-Sulṭaniyyah as the primary source and places it in dialogue with contemporary theories of political legitimacy and representation. The findings reveal that political legitimacy in Al-Mawardi’s thought is constructed through the integration of Islamic legal principles, leadership competence, and public recognition. At the same time, Ahl al-Hall wa al-‘Aqd serves as a representative mechanism grounded in competence, integrity, accountability, and the pursuit of the common good (maslaḥah). The novelty of this study lies in reinterpreting Ahl al-Hall wa al-‘Aqd as an ethical framework of political representation and reconstructing Al-Mawardi’s political thought through the concepts of normative-representative legitimacy and normative-meritocratic representation. These conceptual contributions enrich both Islamic political thought and contemporary theories of representative democracy.